Risk Analysis of Exposure to NH3 And H2S Gas to Workers in The Small Industrial Environment of Magetan Regency in 2021 - Rina Yuliarti; Khambali Khambali; Rusmiati Rusmiati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
ABSTRACT Decomposition of fur, meat, and skin residues produces NH3 and H2S gases that may pose a risk to worker health. NH3 gas is a gas that has a characteristic pungent odor, is corrosive, and is highly toxic even in low concentrations. Exposure to H2S gas can cause bad effects on health because it is quickly absorbed by the lungs. This study aims to analyze and determine the risk of exposure to NH3 and H2S gases to workers' health in the Magetan Regency Small Industrial Environment (LIK). The design of this study is descriptive-quantitative, that is, a study that aims to describe or characterize an event that occurs in numerical and narrative form. The study used a cross-sectional temporal approach and an environmental health risk analysis (ARKL) approach. The sample consisted of 13 workers. Air samples were collected from a site where the leather tanning process was conducted in the unbundling phase. The data analysis method used is the risk analysis to determine the risk characterization of workers in the small industrial environment (LIK) Magetan. Based on ARKL guidelines, the level of risk is called